Preventing Foodborne Illness: Bacillus cereus - Keith R. Schneider; Renée Goodrich Schneider; Rachael Silverberg; Ploy Kurdmongkoltham; Bruna Bertoldi (EDIS)
Ingesting foods contaminated with Bacillus cereus bacteria can lead to nausea, vomiting, abdominal cramps, and diarrhea. Though B. cereus is commonly found in many types of fresh and processed foods, proper cooking, handling, and storage can minimize the risk of contamination. This revised 6-page fact sheet explains how B. cereus is transmitted, what foods it is commonly associated with, the methods used to prevent contamination, and good practices for receiving, handling, processing, and storing food. Written by Keith R. Schneider, Renée Goodrich Schneider, Rachael Silverberg, Ploy Kurdmongkoltham, and Bruna Bertoldi, and published by the Department of Food Science and Human Nutrition, April 2017.